Implementation of Independent Curriculum Learning at Cimone State Elementary School Tangerang - Alfiatun Najah, Mia; Nuraeni, Yeni; Magdalena, Ina (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The present study investigates the implementation of the Independent Curriculum at SDN Cimone 1. It uses a qualitative descriptive approach, collecting data through observation, interviews, and documentation. The school's efforts face various challenges, including the readiness of teachers and principals to carry out the programme. The Merdeka Curriculum emphasises flexibility, independence, and character development, making learning more relevant, adaptable, and enjoyable for students. The study's findings indicate that implementing this curriculum depends on active teaching, available resources, and the diverse learning needs of students. Teachers need to be more creative and adaptable in managing project-based learning, while students respond positively as they feel freer to express their interests and talents. Challenges include limited facilities, uneven teacher readiness, and students adapting to new and innovative teaching methods. Strengthening teacher training, acquiring facilities, and fostering greater collaboration between schools and stakeholders are essential to ensure the curriculum’s effective implementation and to produce a positive impact on the overall learning experience in elementary schools.